Persuasive Language in Wonderful Indonesia’s Top Destination - Mella Narolita; Rahmi Fadhella (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study examines persuasive language in the Top Destinations section of the Wonderful Indonesia website. Official tourism websites are important because they provide travel information and shape destination image through promotional discourse. This research aims to identify the persuasive lexical choices, sentence patterns, and projected image themes used in the destination descriptions. The study employed a descriptive qualitative method with discourse analysis. The data were taken from nine selected destination descriptions on the official Wonderful Indonesia website, collected through documentation and note-taking. The analysis focused on words, phrases, clauses, and sentences that contain persuasive meaning. The findings show that the descriptions rely on positive adjectives, evaluative nouns, and attractive verbs to present destinations as beautiful, unique, prestigious, and memorable. The texts use declarative promotional patterns, recommendation structures, reader-oriented expressions, and imperatives to engage readers and encourage positive evaluations. These linguistic features construct recurring image themes of natural beauty, cultural richness, adventure, uniqueness, leisure, and prestige. The features project Indonesia as a diverse and attractive tourism destination. These results show how concise destination blurbs function as persuasive discourse in official tourism promotion.